Methods for assessing DNA fragmentation in bovine spermatozoa: A Mini-review of Indonesian research - Satrio , Faisal Amri; Magfira; Karja , Ni Wayan Kurniani (ARSHI Veterinary Letters, 2025)
This article reviews research methods and analyses of bovine sperm DNA fragmentation conducted in Indonesia. A literature review using Google Scholar identified 37 articles by Indonesian authors published since 2018, with a peak of eight articles in 2023. The primary techniques employed include Acridine Orange staining (17 articles), Sperm-Bos-Halomax kits (12 articles), Toluidine Blue staining (7 articles), and the TUNEL assay (1 article), each exhibiting methodological variations. This review provides a valuable reference for stakeholders aiming to develop standardised regulations for semen evaluation in cattle.